Soil microbiota and microarthropod communities in oil contaminated sites in the European Subarctic - E. N. Melekhina (Nature Portfolio, 2021)
Abstract The present comprehensive study aimed to estimate the aftermath of oil contamination and the efficacy of removing the upper level of polluted soil under the conditions of the extreme northern taiga of northeastern European Russia. Soil samples from three sites were studied. Two sites were contaminated with the contents of a nearby sludge collector five years prior to sampling. The highly contaminated upper soil level was removed from one of them. The other was left for self-restoration. A chemical analysis of the soils was conducted, and changes in the composition of the soil zoocoenosis and bacterial and fungal microbiota were investigated. At both contaminated sites, a decrease in the abundance and taxonomic diversity of indicator groups of soil fauna, oribatid mites and collembolans compared to the background site were found. The pioneer eurytopic species Oppiella nova, Proisotoma minima and Xenyllodes armatus formed the basis of the microarthropod populations in the contaminated soil. A complete change in the composition of dominant taxonomic units was observed in the microbiota, both the bacterial and fungal communities. There was an increase in the proportion of representatives of Proteobacteria and Actinobacteria in polluted soils compared to the background community. Hydrocarbon-degrading bacteria—Alcanivorax, Rhodanobacter ginsengisoli, Acidobacterium capsulatum, and Acidocella—and fungi—Amorphotheca resinae abundances greatly increased in oil-contaminated soil. Moreover, among both bacteria and fungi, a sharp increase in the abundance of uncultivated organisms that deserve additional attention as potential oil degraders or organisms with a high resistance to oil contamination were observed. The removal of the upper soil level was partly effective in terms of decreasing the oil product concentration (from approximately 21 to 2.6 g/kg of soil) and preventing a decrease in taxonomic richness but did not prevent alterations in the composition of the microbiota or zoocoenosis.